The rise of Eastern Europe and German labor market reform: Dissecting their effects on employment - Timo Walter (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2021)
From the early 1990s until 2005 the unemployment rate rose in Germany from 7.3% to 11.7%. While the unemployment rate reached its peak in 2005, it decreased steadily in the following years. On the one hand, the fourth stage of the German labor market reform (Hartz IV) was implemented in 2005 with the intent to cut the unemployment rate. On the other hand, the productivities in Germany and Eastern Europe grew strongly during the same period, enhancing the joint trade. The "rise of the East", in terms of rising trade, is likely to have had an ambiguous effect on the German labor market. This paper investigates the employment effects of the "Hartz IV-Reform". Further, it concentrates on the labor market effects of the German and Eastern European productivity shock. The focus lies on the national and county level (including 402 counties). As the effects on regional labor markets differ and take time, the paper builds on the dynamic and spatial trade model of Caliendo et al. (2019). I find that the "Hartz IV-Reform" and the German productivity contributes positively to the decline of unemployment, whereas the increase in Eastern European productivity is only responsible for a minor increase in unemployment.
urn:nbn:de:bsz:100-opus-19362
Keywords: F14; F16; F17; 330; Dynamic Trade Model; Labor Market Reform; Trade Liberalization; Productivity Shocks; Germany; Eastern Europe